The Role of Intertheoretical Connections in the System of Sciences (by the Example of Applying the Information Approach to the Theory of Evolution) - A. Yu. Storozhuk (Дискурс, 2019)
Introduction. The process of intertheoretical adaptation of the conceptual apparatus is considered on the example of transferring the terminology of information theory and thermodynamics to the field of evolution theory. The author analyzes the grounds for such adaptation, its validity and epistemological justification. Methodology and sources. Methodologically, the work is based on a logical analysis of primary sources and research literature, as well as on the application of philosophical reflection. Results and discussion. The paper shows that conceptual transfer is a type of heuristic that allows one to advance in understanding problems that are not initially solvable within a separate discipline. Reformulation of scientific problems in another language allows us to explain the features of a number of phenomena and better understand their mechanisms. The conceptual transference in the course of intertheoretic adaptation is not complete: some concepts do not find a direct analogy, others change their original meaning and have a limited scope. The disadvantage of conceptual adaptation is the insufficient validity of its foundations, since it is often based on informal methods of scientific knowledge, such as analogy, modeling, etc. Conclusion. In the case of stagnation of a mature scientific theory, conceptual can pose new problems and give new methodological approaches, which serves as a new incentive for the development of the established theory